In vivo embryo production in cows superovulated 1 or 2 days after ovum pick-up - Surjus, Ricardo S.; Prata, Alexandre B.; Borsato, Marta; Mattos, Fernanda C. S. Z. [UNESP]; Martins da Silveira, Mariana C. [UNESP]; Mourao, Gerson B.; Pires, Alexandre V.; Wiltbank, Milo C.; Sartori, Roberto (CSIRO Publishing, 2014)
The present study evaluated superovulatory responses and in vivo embryo production in cows treated with FSH starting 1 or 2 days after ovum pick-up (OPU). Thirty-three non-lactating Nelore cows were subjected to aspiration of all follicles >= 3 mm for OPU. After OPU, cows were randomly divided into two groups in which the follicle superstimulatory treatments with FSH started 1 or 2 days after OPU (Groups D1 and D2, respectively). Data are presented as the least squares mean +/- s.e.m. The number of follicles >= 3 mm before OPU was similar between groups (~34); however, cows in Group D2 had more follicles >= 3 mm on the first day of FSH (15.2 +/- 2.3 vs 7.6 +/- 1.7; P = 0.04) and a higher ratio of the number of follicles at first FSH/number of follicles before OPU (0.41 +/- 0.04 vs 0.24 +/- 0.02; P = 0.01). In addition, Group D2 cows had a greater superovulatory response than did cows in Group D1 (18.9 +/- 2.8 vs 9.1 +/- 1.9 corpora lutea, respectively; P < 0.03). However, there was no difference in the total number of recovered ova and embryos from cows in Groups D2 and D1 (5.1 +/- 1.4 vs 4.9 +/- 1.3, respectively; P > 0.10). Nevertheless Group D2 cows had more freezable embryos than Group D1 cows (3.2 +/- 1.1 vs 1.3 +/- 0.5, respectively; P < 0.05). Cows from Group D2 had a much higher proportion (P < 0.001) of follicles >= 8 mm compared with follicles >= 6 mm and <8 mm at the time of the last treatment with FSH. In conclusion, to obtain a greater production of viable embryos in superovulated cows after OPU, it is recommended to wait at least 2 days before starting FSH treatment.
Keywords: cattle, follicle aspiration, FSH.